Present status of traditional fish drying activities and women participation in Chalan Beel area of Natore and Pabna district in Bangladesh - Rhaman, Mahbuba; Hossain, Md Rayhan; Flowra, Fawzia Adib; dey, Shishir Kumar; Sultana, Sayeeda (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
This study focuses mainly on the traditional fish drying activities and role of women in fish drying sector in Chalanbeel area of northern part of Bangladesh. The study covers three different drying spots of Natore and Pabna districts. A total of 13 dried fish producer, 18 male worker and 27 female workers were selected for the study. The study was conducted over a period of six month from September to February 2014. In these study areas, sun drying of fish is generally carried out on bamboo made rack. Total 21 species were gradually used for drying selected from the local fish market and directly from the fishermen of Chalanbeel. The amount of salt used in fish drying ranges 2-4kg/40 kg fish. The dried fishes were bagged into a plastic and jute bags. The dried fish producers usually sell their products weekly from their storage. The lowest price of dried fish is 300-400 Tk./ kg for Punti and highest is 800 Tk./kg for Boal. The monthly production of the study areas ranges 1.8-4.00 mt. However, women play a significant role in dry fish processing. The paper points out that the sample women are involved in different income generating activities like drying, sorting and grading, cleaning and salting and monthly income derived from those activities vary in peak and lean season. The paper also identifies that the highest 51.85% women were found in 25-40 years age groups and the lowest 7.41% was found in 50-70 years age group and also 40.74% was found in 10-25 years age group which were (children) involved in drying activities instead of spending time in school. In the study areas 55.56% women were married, 40.74% were unmarried and 3.70% were widow. The highest percentage of family type (59.26%) was found as nuclear and the joint family was 40.74%. The educational status of women in drying point was 40.74% illiterate, 37.04% had education up to primary level 11.11% capable of sign only and 11.11% reach up to secondary level. Most of the respondents live in kacha house.59.26% of housing condition were kacha, 22.22% were semi-pucca and 18.52% were pucca. 33.33% people used own-tube well and 59.26% people used others-tube well for drinking water and household purposes while 7.41% used kua. From the study, it was found that 70.37% respondents had electricity connection and 29.63% had no electricity connection. In study areas, 59.26% respondents use defected semipucca, 29.63% respondents use kacha and 11.11% respondents use pucca sanitary latrine. In both study area, 100% of interviewed respondents were Muslim with no other religious person. Asian Australas. J. Biosci. Biotechnol. 2017, 2 (1), 89-99